Creating therapeutic relationships through communication: a qualitative metasynthesis from the perspectives of people with communication impairment after stroke. Issue 12 (5th June 2022) - Bright, F. A. S.; Reeves, B.
Abstract: Purpose: Communication between patients and clinicians influences the development of therapeutic relationships. Communication is disrupted when the patient has communication impairments after stroke. However, how these communication disruptions influence therapeutic relationships is not well-understood. This qualitative metasynthesis explores the perspectives of people with communication impairment to understand how interpersonal communication influences therapeutic relationships. Material and methods: Four databases were searched for qualitative studies which discussed how communication influenced therapeutic relationships from the perspectives of people with aphasia, dysarthria or apraxia of speech. Additional papers were identified through citation searching and subject experts. Nineteen eligible papers were included and analysed using thematic analysis. Results: Four themes were constructed from the analysis: (1) Relationships provide the foundation for rehabilitation; (2) Different relational possibilities arise from "reading" the clinician; (3) Creating therapeutic relationships through validating interactions and connections; and (4) Creating therapeutic disconnections through invalidating, exclusionary interactions. Conclusions: A therapeutic relationship develops, at least in part, in response to the clinician's communication and how this is received and experienced by the patient. Understanding the characteristics of relationship-fostering communication and knowing how communication influences relationships can help clinicians critically reflect on their communication and better develop therapeutic relationships with people with communication impairment. IMPLICATIONS FOR REHABILITATION: Practitioner-patient communication can facilitate therapeutic relationships or create therapeutic disconnections. Communication patterns that are commonly evident when a patient has communication impairments can impede therapeutic relationships. Clinicians need to attend to how their communication is received and how it influences people's sense of self. Communication partner training should address the existential and relational needs of people with communication impairment after stroke.